Validation of the liver traffic light test as a predictive model for survival and development of liver‐related events. Issue 5 (27th March 2021) - Sylvester, Rochelle; Hydes, Theresa J; Hales, Alan; Williams, Roger; Sheron, Nick
Abstract: Background and Aim: Liver disease mortality rates continue to rise due to late diagnosis. We need noninvasive tests to be made available in the community that can identify patients at risk from a serious liver‐related event (SLE). We examine the performance of a blood test, the liver traffic light test (LTLT), with regard to its ability to predict survival and SLEs. Methods: Using routinely gathered clinical data, sequential LTLT test results from 4854 individuals with suspected liver disease were prospectively analyzed (median follow‐up 41 months). An SLE was defined as the development of cirrhosis, liver failure, ascites, or varices. Patients were graded as follows: red (high risk), amber (intermediate risk), and green (low risk). Results: Overall, 565 individuals experienced an SLE (11.6%). The area under the curve (AUC) for the continuous LTLT variable was 0.87 (95% confidence interval 0.85–0.89) for prediction of an SLE and 0.81 (0.78–0.84) for mortality. When categorized into red/amber/green grades, a red LTLT result predicted an SLE with negative and positive predictive values of 0.97 and 0.29, respectively. A red LTLT score predicted mortality with negative and positive predictive values of 0.98 and 0.18, respectively. Kaplan–Meier plots demonstrated increased mortality and SLEs in the red group versus the green and amber groups ( P  < 0.001) and an increase in SLEs in the amber versus green group ( P  < 0.001). Conclusion: Here, the LTLT is further validated for the prediction of survival and SLE development. The LTLT could aid primary care risk management and referral pathways with the aim of detecting and treating liver disease earlier in the general population. Abstract : In this study, we assess the accuracy of the liver traffic light test (LTLT) for the prediction of serious liver‐related events (SLE) (cirrhosis, liver failure, ascites, or varices) and mortality in a cohort of 4854 individuals with risk factors for liver disease identified from both the community and secondary care. The area under the curve for the continuous LTLT variable was 0.87 (0.85–0.89) for prediction of an SLE and 0.81 (0.78–0.84) for mortality. When categorized into red/amber/green grades, a red LTLT result predicted an SLE with negative and positive predictive values of 0.97 and 0.29, respectively.